The Socio‐Economic Profiles of Small and Medium‐Sized Towns: Insights from European Case Studies. (27th February 2017) - Hamdouch, Abdelillah; Demaziere, Christophe; Banovac, Ksenija
Abstract: This paper is part of the research on functional roles of European towns conducted by a group of researchers gathered around the ESPON project 'TOWN'. Building on the systematic analysis of the socio‐economic dynamics of 31 European small and medium‐sized towns (SMSTs), we identified three profiles of their local economies. The first profile is defined as a dominant 'residential' economy that mostly relies on local activities that satisfy the needs of people in an area (residents, commuters or tourists). The second profile corresponds to a dominant 'productive' economy based on the production of goods and services to be mainly exported and consumed out of its area. The third profile is the mixed type that is characterised by an important share of activities in productive and residential sector with a complementary 'creative‐knowledge' dimension, based on entrepreneurship, creativity and collaboration in innovation. Moreover, we analysed the economic performance and the shift in profiles in order to detect in which way towns make choices between residential economy, competitiveness and innovation for their local development.